Amyloid A Amyloidosis After Renal Transplantation: An Important Cause of Mortality - MİRİOĞLU, ŞAFAK; Sarıhan, Elif İrem; Çalışkan, Yaşar Kerem; Mirioğlu, Şafak; Özlük, Yasemin; Şenateş, Banu; Seyahi, Nurhan; Baştürk, Taner; Yıldız, Abdülmecit; Kılıçaslan, Işın; Sever, Mehmet Şükrü (My University, 2020)
Background. There are limited data on the outcome of transplant recipients with familial Mediterranean fever (FMF)-associated AA amyloidosis. The aim of the present study is to evaluate demographic, clinical, laboratory, and prognostic characteristics and outcome measures of these patients. Methods. Eighty-one renal transplant recipients with FMF-associated AA amyloidosis (group 1) and propensity score-matched transplant recipients (group 2, n = 81) with nonamyloidosis etiologies were evaluated in this retrospective, multicenter study. Recurrence of AA amyloidosis was diagnosed in 21 patients (group 1a), and their features were compared with 21 propensity score-matched recipients with FMF amyloidosis with no laboratory signs of recurrence (group 1b). Results. The risk of overall allograft loss was higher in group 1 compared with group 2 (25 [30.9%] versus 12 [14.8%];P= 0.015 [hazard ratio, 2.083; 95% confidence interval, 1.126-3.856]). Patients in group 1 were characterized by an increased risk of mortality compared with group 2 (11 [13.6%] versus 0%;P= 0.001 [hazard ratio, 1.136; 95% confidence interval, 1.058-1.207]). Kaplan-Meier analysis revealed that 5- and 10-year patient survival rates in group 1 (92.5% and 70.4%) were significantly lower than in group 2 (100% and 100%;P= 0.026 andP= 0.023, respectively). Although not reaching significance, overall, 5- and 10-year graft survival rates (57.1%, 94.7%, and 53.8%, respectively) in group 1a were worse than in group 1b (76.2%, 95%, and 77.8%, respectively;P= 0.19,P= 0.95, andP= 0.27, respectively). Conclusions. AA amyloidosis is associated with higher risk of mortality after kidney transplantation. Inflammatory indicators should be monitored closely, and persistent high levels of acute-phase reactants should raise concerns about amyloid recurrence in allograft.